2017
DOI: 10.3389/fpsyg.2017.01078
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Expertise in Joint and Solo-Improvisation

Abstract: Joint-improvisation is not only an open-ended creative action that two or more people perform together in the context of an artistic performance (e.g., theatre, music or dance). Joint-improvisation also takes place in daily life activities when humans take part in collective performance such as toddlers at play or adults engaged in a conversation. In the context of this article, joint-improvisation has been looked at from a social motor coordination perspective. In the literature, the nature of the social moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…There are good reasons to believe that improvisational skills, similarly to emotions or intentions, color movements. For example, it has been empirically demonstrated that movement qualities of expert improvisers differ from those of novices (Noy et al, 2011; Issartel et al, 2017). Using the mirror game (Noy et al, 2011), a simple yet effective paradigm for studying two people improvising hand movements with different social roles (leader/follower/no designated leader), Noy et al (2011) found that experts create more complex (i.e., creative) and synchronized motion than novices when there is no designated leader.…”
Section: A New Approach To Improvisation Grounded On Motor Componentmentioning
confidence: 99%
See 3 more Smart Citations
“…There are good reasons to believe that improvisational skills, similarly to emotions or intentions, color movements. For example, it has been empirically demonstrated that movement qualities of expert improvisers differ from those of novices (Noy et al, 2011; Issartel et al, 2017). Using the mirror game (Noy et al, 2011), a simple yet effective paradigm for studying two people improvising hand movements with different social roles (leader/follower/no designated leader), Noy et al (2011) found that experts create more complex (i.e., creative) and synchronized motion than novices when there is no designated leader.…”
Section: A New Approach To Improvisation Grounded On Motor Componentmentioning
confidence: 99%
“…Using the mirror game (Noy et al, 2011), a simple yet effective paradigm for studying two people improvising hand movements with different social roles (leader/follower/no designated leader), Noy et al (2011) found that experts create more complex (i.e., creative) and synchronized motion than novices when there is no designated leader. In another behavioral study, Issartel et al (2017) compared motion characteristics in the mirror game of three groups with distinct levels of expertise in improvisation dance (novice, intermediate, expert). Results revealed that each group had a very specific movement organization and that motor creativity increased with expertise.…”
Section: A New Approach To Improvisation Grounded On Motor Componentmentioning
confidence: 99%
See 2 more Smart Citations
“…Improvisation studies across many disciplines (dance, art, and conversation) have identified the psychosocial mechanisms of joint creative processes which make up a continual feedback loop: One attends to the actions of their partner, then modulates their own actions and updates their anticipation of partner actions. Interestingly, empirical work finds that the more that dancers anticipate their partners' movements, the more they kept their own movement signature (Issartel et al 2017), and that arbitrary selection of a leader in improvisational tasks degrades partnership performance (Noy et al 2011). In long-term partnerships, through egalitarian improvisation, each partner can act more like themselves and transcend the narrative of compromised identity in relationships.…”
Section: Partner Improvisationmentioning
confidence: 99%